Sicca Syndrome Associated with Immune Checkpoint Inhibitor Therapy. (17th April 2019) - Warner, Blake M.; Baer, Alan N.; Lipson, Evan J.; Allen, Clint; Hinrichs, Christian; Rajan, Arun; Pelayo, Eileen; Beach, Margaret; Gulley, James L.; Madan, Ravi A.; Feliciano, Josephine; Grisius, Margaret; et al.
Abstract: Background: The objective of this study was to characterize the clinicopathologic features of sicca syndrome associated with immune checkpoint inhibitor (ICI) therapy. Subjects, Materials, and Methods: Consecutive patients with new or worsening xerostomia in the setting of ICI treatment for benign or malignant neoplastic disease were evaluated, including labial salivary gland biopsy (LSGB). Results: Twenty patients (14 male; median age 57 years) had metastatic melanoma ( n = 10), metastatic carcinoma ( n = 6), or recurrent respiratory papillomatosis ( n = 4) and were being treated with avelumab ( n = 8), nivolumab ( n = 5), pembrolizumab ( n = 4), nivolumab/ipilimumab ( n = 2), and M7824, a biologic targeting programmed cell death ligand 1 (PD‐L1) and transforming growth factor ß ( n = 1). Four had pre‐existing autoimmune disease. Nineteen had very low whole unstimulated saliva flow; six had new dry eye symptoms. The median interval between ICI initiation and dry mouth onset was 70 days. Rheumatoid factor and anti‐Sjögren's Syndrome‐related Antigen A (Anti‐SSA) were both positive in two subjects. LSGB showed mild‐to‐severe sialadenitis with diffuse lymphocytic infiltration and architectural distortion. There were lymphocytic aggregates in eight patients, composed mainly of CD3 + T cells with a slight predominance of CD4 + over CD8 + T cells. ICI targets (e.g., programmed cell death 1 and PD‐L1) were variably positive. In direct response to the advent of the sicca immune‐related adverse event, the ICI was held in 12 patients and corticosteroids were initiated in 10. Subjective improvement in symptoms was achieved in the majority; however, salivary secretion remained very low. Conclusion: ICI therapy is associated with an autoimmune‐induced sicca syndrome distinct from Sjögren's syndrome, often abrupt in onset, usually developing within the first 3 months of treatment, and associated with sialadenitis and glandular injury. Improvement can be achieved with a graded approach depending on severity, including withholding the ICI and initiating corticosteroids. However, profound salivary flow deficits may be long term. Implications for Practice: Sicca syndrome has been reported as an immune‐related adverse event (irAE) of immune checkpoint inhibitor therapy (ICI) for neoplastic diseases. Severe dry mouth (interfering with eating or sleeping) developed abruptly, typically within 90 days, after initiation of ICI therapy. Salivary gland biopsies demonstrated mild‐to‐severe sialadenitis distinct from Sjögren's syndrome, with diffuse T‐cell lymphocytic infiltration and acinar injury. Recognition of the cardinal features of ICI‐induced sicca will spur appropriate clinical evaluation and management, including withholding of the ICI and corticosteroid, initiation. This characterization should help oncologists, rheumatologists, and oral medicine specialists better identify patients that develop ICI‐induced sicca to initiate appropriate clinical evaluation and therapy to reduce the likelihood of permanent salivary gland dysfunction. Abstract : Sicca syndrome has been reported as a common complication of immune checkpoint therapy. This article describes the clinicopathologic features of sicca syndrome, with the goal of raising awareness to a encourage early recognition and appropriate management.